Warfighting - Department of the Navy ([Washington, D.C.] U.S. Marine Corps, 1997)
Warfighting was published to establish a Marine Corps philosophy and doctrine presented in an easy-to-read format. Every officer should read and reread this text, to understand it, and to take its message to heart. Warfighting has stimulated discussion and debate from classrooms to wardooms, training areas to combat zones. The philosophy contained in this publication has influenced our approach to every task we have undertaken.
Includes bibliographical references (p. 97-106).
Keywords: United States. Marine Corps -- Handbooks, manuals, etc -- United States. -- Marine Corps -- Handbooks, manuals, etc; Militarism -- United States -- Handbooks, manuals, etc; Military art and science -- United States -- Handbooks, manuals, etc